Decomposition and nutrient release from soybean cut at different growth stages - Padovan, Milton Parron; Almeida, Dejair Lopes de; Guerra, José Guilherme Marinho; Ribeiro, Raul de Lucena Duarte; Oliveira, Fábio Luiz de; Santos, Leandro Azevedo; Alves, Bruno José Rodrigues; Souto, Sebastião Manhães (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the dynamics of decomposition and release of nutrients from aerial plant parts of the soybean cultivar Celeste used as green manure. A randomized block design was adopted with five replications. Soybean plants were cut close to the soil surface 55, 85 and 115 days after emergency (DAE), and analysed to determine their decomposition and release of N, P, K, Ca and Mg, by placing 60 g of fresh material of the aerial part in nylon screen bags, that were distributed on field plots surface . The rates of loss of dry matter and of nutrient release were monitored in the 5, 10, 15, 30, 60, 90, 120 and 150 days after plant cut. The exponential model X = X0e-kt demonstrated that the dynamics of the material cut in the 55, 85 and 115 DAE were not so contrasting. The climate could have interfered on the results, principally on K release rates, however it did not cause mean differences on the biomass decomposition and N and P release. Soybean plant material from cut plants, at different growth stages, present similar rates of decomposition and nutrient release.
Keywords: Glycine max; decomposition dynamics; half-life time; organic agriculture